Patrón de Presentación de Apendicitis en el Hospital Provincial Julius Doepfner de la provincia de Zamora Chinchipe en el periodo 2011 hasta 2015 - Apolo Fuentes, Gustavo Alexei (2018)
Abstract:In the present descriptive, retrospective, observational cross - sectional study, the pattern of presentation of appendicitis was established at the Julius Doepfner Hospital in the province of Zamora Chinchipe in the period 2011 - 2015, by taking data from clinical records, With the purpose of knowing its presentation at the present time. Of which 294 patients, 61% of whom were men and 39% of the women, were 11 to 15 years of age and 53 patients were the most prevalent range. The stages of presentation of appendicitis, the most prevalent is phase II with 43%. The complications were presented in 6% and the most prevalent is the adynamic associated with peritonitis with 42%. Finally, it was concluded that the pattern of appendicitis of the Julius Doepfner hospital in the province of Zamora Chinchipe has a presentation different from that reported in the literature.